Analisis Pemanfaatan Wordwall sebagai Media Pembelajaran Matematika di MI/SD - Linanda Dian Firdaus; Fadli Nur Hafiz; Sona Niamika; Dian Mustika Anggraini (PT Cendekia Education Center, 2026)
This study aims to analyze the utilization of Wordwall as a mathematics learning medium for second-grade students at MI NU Tsamrotul Wathon. The research employed a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The participants consisted of a second-grade teacher and second-grade students at MI NU Tsamrotul Wathon. The findings revealed that the use of Wordwall in mathematics learning positively contributed to increasing students learning motivation, activeness, and enthusiasm during the learning process. Wordwall was implemented through interactive quizzes and educational games that were adjusted to the learning materials. The learning activities became more engaging and enjoyable, encouraging students to actively participate, answer questions, and complete assignments. The teacher reported that students who previously showed low interest and concentration in mathematics became more focused and motivated after the implementation of Wordwall. Furthermore, the interactive features of Wordwall helped students understand mathematical concepts more easily and created a positive learning atmosphere. Therefore, Wordwall can be considered an effective and innovative learning medium to support mathematics learning and improve student engagement at the elementary school level.